2019
DOI: 10.1017/cjn.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Cerebrospinal Fluid Total Protein Upper Limits in Canada: Time for an Update?

Abstract: ABSTRACT:Background: The antiquated standard reference range of 0.15–0.45 g/L for cerebrospinal fluid total protein (CSF-TP) is well entrenched in medical literature and laboratory operating procedures across the world. Methods: We conducted a web-based survey with a response rate of 34.9% through the listserv of the Canadian Neurological Sciences Federation. Additional laboratory reference data were collated by telephone interview of hospital laboratory technologists across Canada. Results: A total of 142 sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The current gold standard, the reference range of 15-45 mg/dL (0.15-0.45 g/L) for lumbar CSF-TP dates back to 1938, and it has been adopted for a wide range of population for almost a century [1,2]. However, recent Western studies have started to report that the concentration of CSF-TP in adults is considered to increase gradually with age, and the concentrations in the older population are significantly higher than the current standard upper reference limit [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current gold standard, the reference range of 15-45 mg/dL (0.15-0.45 g/L) for lumbar CSF-TP dates back to 1938, and it has been adopted for a wide range of population for almost a century [1,2]. However, recent Western studies have started to report that the concentration of CSF-TP in adults is considered to increase gradually with age, and the concentrations in the older population are significantly higher than the current standard upper reference limit [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only two studies have reported on CSF-TP in Japanese patients, but these were presented over 30 years ago [11,12]. Since the CSF measuring methods and the accuracy of testing have been greatly improved in the past decades, it is crucial to review the CSF-TP reference interval for various populations [2,11,12]. In addition, even though the available data from a healthy population are often limited [1,3,6,13] because of the invasive nature and the potential risks of the sampling procedure, using the data of healthy subjects is desirable to properly interpret the laboratory data [14].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the concentration of cerebrospinal fluid total protein (CSF-TP) is used for the diagnosis of various life-threatening neurological emergencies, such as infectious, inflammatory, and immune diseases of the central/peripheral nervous systems; thus, a valid reference interval of CSF-TP concentrations is crucial for precise diagnosis and treatment. The current gold standard, the reference range of 15-45 mg/dL (0.15-0.45 g/L) for lumbar CSF-TP dates back to 1938, and it has been adopted for a wide range of population for almost a century [1,2]. However, recent Western studies have started to report that the concentration of CSF-TP in adults is considered to increase gradually with age, and the concentrations in the older population are significantly higher than the current standard upper reference limit [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%